213 Eating Patterns Associated with Sleep Duration, Insomnia, Daytime Sleepiness and Overall Sleep Quality at the US-Mexico Border. (3rd May 2021) - Ghani, Sadia; Delgadillo, Marcos; Granados, Karla; Okuagu, Ashley; Wills, Chloe; Alfonso-Miller, Pamela; Buxton, Orfeu; Patel, Sanjay; Parthasarathy, Sairam; Haynes, Patricia; Molina, Patricia; Seixas, Azizi; et al.
Abstract: Introduction: Previous studies have linked sleep to risk of diabetes and obesity, at least partially via alterations in food intake. Diabetes and obesity are common among Hispanics/Latinos, and studies are needed to better clarify the role of sleep for health among this group. Methods: Data were collected from N=100 adults (age 18-60, 47% female) of Mexican descent in the city of Nogales, AZ (34% not born in the US). Surveys were presented in English or Spanish. Eating Patterns were assessed with the Three-Factor Eating Questionnaire (TFEQ), which resulted in a total score and subscales for "cognitive restraint, " "uncontrolled eating, "and "emotional eating." Insomnia was assessed with the use of the Insomnia Severity Index (ISI), Sleepiness with the use of the Epworth Sleepiness Scale (ESS), Sleep quality with the use of the Pittsburgh Sleep Quality Index (PSQI), and weekday and weekend sleep duration with the use of the Sleep Timing Questionnaire (STQ). Covariates included: age, sex, Body Mass Index (BMI), education and immigrant status. Results: When adjusted for age, sex and immigrant status (model-1), eating patterns were associated with greater insomnia (95%CI:[0.066, 1.095];p=0.027), poorer sleep quality (95%CI:[0.170, 1.456];p=0.014), sleepiness (95%CI[0.032, 1.026];p=0.037), and weekend (but not weekday) sleep duration (95%CI:[-0.031, 0.003];p=0.015). Further adjustment for education (model-2) revealed similar significant associations. Additional adjustment for BMI (model-3) revealed a change in daytime sleepiness, where no association was seen (95%CI:[-0.202, 0.805];p=0.238). Regarding subscale scores, relationships were generally seen between sleep and both emotional eating and uncontrolled eating, but not cognitive restraint. However, after adjustment for BMI, there was a significant association between cognitive restraint and weekend sleep duration (95%CI:[-0.015, -0.001];p=0.030). Conclusion: Greater insomnia, poorer sleep quality, increased daytime sleepiness and decreased weekend sleep duration were associated with eating patterns at the US Mexico border, particularly in terms of uncontrolled eating and emotional eating. This suggests possible mechanisms linking sleep and obesity in Hispanic/Latinos. Support (if any): Supported by T32HL007249, R01MD011600, R01DA051321